(untitled) (Trabalho & Educação, 2016)
The main aim of this article is to address the importance of work centrality as a basis for the design of an education project that can contribute to a new form of sociability. From Marx’s conception of work as the fundamental ontological category, once it promotes men from its condition of a natural being into the condition of a social being, as it is through the relation human/nature mediated by work that human beings to transform nature and consequently transform themselves. There is a movement of denial of work as an analytical category when the politics centrality is highlighted as a democratic strategy to transform society, rather than the revolutionary perspective. Such inversion shows a reformist-conservative view by considering that democratic achievements shall result in a social order which is emancipated as well as free of contradictions and inequalities. Through some bibliographic and documental research, this work points out the numerous studies which emphasize the importance of participation, citizenship, democracy, pluralism, tolerance, small group movements (race, gender, ethnicity etc.), as a consequence of the politics centrality in the education area, and many times substitute the political movement of the social classes. There is some concern in producing a conceptual framework that hides the class struggle and naturalizes the structural parameters of a capitalist society. Thus, the ideology that adapts to the capitalist form of sociability, even if it is considered critical, limits the analysis to the system superficial manifestations, without really reaching antagonisms which determine the main social problems. ___ O objetivo central do presente artigo é tratar da importância da centralidade do trabalho como pressuposto para o delineamento de um projeto de educação que contribua para uma nova forma de sociabilidade. Partimos da concepção marxiana de que o trabalho é a categoria ontológica fundamental porque eleva o homem da sua condição de ser natural para ser social, visto que é através da relação do homem com a natureza, pelo trabalho, que ele transforma a natureza, transformando, portanto, a si mesmo. Há um movimento de negação do trabalho como categoria analítica ao se destacar a centralidade da política como estratégia democrática para a transformação social, em lugar da perspectiva revolucionária. Tal inversão possui um viés reformista-conservador por considerar que as conquistas democráticas conduzirão a uma ordem social emancipada e livre de contradições e desigualdades. Por meio de estudo bibliográfico e documental, destacamos, como consequência da centralidade da política no campo da educação, a profusão de estudos que enaltecem a importância da participação, da cidadania, da democracia, do pluralismo, da tolerância, dos pequenos movimentos grupais (raça, gênero, etnia etc.) e substituem, por vezes, o movimento político das classes sociais. Há uma preocupação em se produzir um quadro conceitual que obscureça a luta de classes e naturalize os parâmetros estruturais da sociedade capitalista. Assim, a ideologia que se adapta à forma de sociabilidade capitalista, ainda que seja considerada crítica, restringe as análises às manifestações superficiais do sistema, sem tocar nos antagonismos determinantes dos principais problemas sociais.